Insight into atmospheric pitting corrosion of carbon steel via a dual-beam FIB/SEM system associated with high-resolution TEM. (15th May 2019) - Wan, Ye; Tan, Jun; Zhu, Siteng; Cui, Jingping; Zhang, Ke; Wang, Xiumei; Shen, Xuanyu; Li, Yanbo; Zhu, Xu
Highlights: Identification of the self-catalytic characteristics in the pitting cavity. Discovery of high chloride and no oxygen in the pitting cavity. Exploration of core-shell chemical and structural distribution in pitting corrosion. Revelation of the porous core being rich in chloride and the shell being rich in oxygen in pitting corrosion. Insight into the pitting microstructures with a ferric chloride core and an iron oxide shell. Abstract: Carbon steel experiences serious pitting corrosion in the atmospheres containing chloride ions. The present research is focused on revealing a three-dimensional chemical and microstructural insight into pitting corrosion with high spatial resolution nano-tomography by addressing 1018 carbon steel after exposed in the marine atmosphere. A well-defined core-shell structure for pitting corrosion products was revealed by using a combination of dual-beam focused ion beam system with scanning electron microscope (FIB/SEM) and high-resolution transmission electron microscope (HRTEM). The core is made of ferric chloride and the shell is constituted with iron oxides. Pitting corrosion is a self-catalytic process and the corrosion products grow to be porous flower-type structures. The porosity in the core provides a diffusion path for the ions. Inclusions promote pitting corrosion growth.